Elastic and plastic buckling of spherical shells under various loading conditions. - Nayyeri Amiri, Shahin (Kansas State University, 2011)
Spherical shells are widely used in aerospace, mechanical, marine, and other industrial applications. Accordingly, the accurate determination of their behavior becomes more and more important. One of the most important problems in spherical shell behavior is the determination of buckling loads either experimentally or theoretically. Therefore, in this study some elastic and plastic buckling problems associated with spherical shells are investigated. The first part of this research study presents the analytical, numerical, and experimental results of moderately thick and thin hemispherical metal shells into the plastic buckling range illustrating the importance of geometry changes on the buckling load. The hemispherical shell is rigidly supported around the base circumference against horizontal translation and the load is vertically applied by a rigid cylindrical boss (Loading actuator) at the apex. Kinematics stages of initial buckling and subsequent propagation of plastic deformation for a rigid-perfectly plastic shell models are formulated on the basis of Drucker- Shield's limited interaction yield condition. The effect of the radius of the boss used to apply the loading, on the initial and subsequent collapse load is studied. In the numerical model, the material is assumed to be isotropic and linear elastic perfectly plastic without strain hardening obeying the Tresca or Von Mises yield criterion. Finally, the results of the analytical solution are compared and verified with the numerical results using ABAQUS software and experimental findings. Good agreement is observed between the load-deflection curves obtained using three different fundamental approaches. In the second part, the Southwell’s nondestructive method for columns is analytically extended to spherical shells subjected to uniform external pressure acting radially. Subsequently finite element simulation and experimental work shown that the theory is applicable to spherical shells with an arbitrary axi-symmetrical loading too. The results showed that the technique provides a useful estimate of the elastic buckling load provided care is taken in interpreting the results. The usefulness of the method lies in its generality, simplicity and in the fact that, it is non-destructive. Moreover, it does not make any assumption regarding the number of buckling waves or the exact localization of buckling
Keywords: Plastic buckling; Spherical shellsElastic; Civil Engineering (0543)